An assessment of dietary patterns and micronutrient intake among farming adults in Rural Sri Lanka - Joyce, Caroline A.; Gelli, Aulo; Caswell, Bess L.; Hess, Sonja Y.; Sitisekara, Hasara; Tan, Xiuping; Jayatissa, Renuka; Peiris, Kalana; Silva, Renuka; Olney, Deanna K. (Elsevier, 2024)
Objectives: The study aimed to characterize food group intake and estimate usual nutrient intakes among Sri Lankan farmers. Methods: A baseline study (Dec 2020-Feb 2021), conducted as part of WFP’s Resilience, Risk Reduction, Recovery, Reconstruction, and Nutrition (R5N) program evaluation, collected data from adults in 45 rural villages across Sri Lanka (N=1283). Dietary intake was assessed using telephone-based 24-hour recalls, with repeat recalls from 60% of respondents (n=769). Reported foods were converted to nutrient intakes using standard recipes and Sri Lankan food composition data. Descriptive statistics were used to calculate average intake of food groups and the relative contribution of food groups to total energy. The National Cancer Institute method was used to estimate mean usual intakes of energy, macro-, and micronutrients, and to calculate the prevalence of adequate intake (PAI) of micronutrients relative to requirements. Results: Grains (primarily rice) and coconut milk provided 56% and 12% of total energy, respectively. Rice (red and white varieties, refined and parboiled), mango, green leafy vegetables, chilies, and fish were the primary sources of micronutrients. Participants reported 118±117 g vegetables and 71±243 g fruit per day (2.4±3.5 servings combined). High consumption of rice contributed to high PAI of riboflavin and thiamine ( >60%). PAI was < 25% for iron, calcium, zinc, niacin, and vitamins C and B12, reflecting low consumption of animal-source foods (ASF; 80 g/day), whole grains, and certain F&V (e.g., citrus fruits). Conclusions: We observed high consumption of rice and coconut milk, and low levels of micronutrient adequacy. Increasing consumption of ASF and F&V is needed to close micronutrient gaps. Staple food fortification may be required to effectively increase the PAI of calcium, iron, zinc, and vitamin B12. Additional research is recommended to understand and address the barriers to low consumption of micronutrient-rich foods.